Effect of waste plastic strip on the shear strength and permeability characteristics of black cotton soil - Hoque, Md. Ikramul; Muzamir, Hasan; Shuvo, Dip Datta (Tamkang University, 2023)
The use of plastic bottles is on the rise, causing lots of new environmental issues. It is now extremely difficult to dispose of plastic waste without damaging the ecosystem. As black cotton soil for embankments and foundations has limited use due to its swelling and hrinkage property as well as its bearing capacity, utilizing plastic bottles to enhance soil strength parameters can be a cost-effective solution. This study investigates the possibility of improving the characteristics of soil by using leftover strips of plastic that have been cut from plastic water bottles. The black cotton soil is amended with about 0%, 5%, 6%, 7%, 8%, 9%, and 10% plastic strips. On the black cotton soil that had been strengthened with plastic waste, direct shear and falling head water permeability tests were executed as part of the experiment. The test results under the circumstances are provided to evaluate the change in soil strength characteristics. In the aspects of shear strength, friction angle, and cohesiveness, it was determined that soil samples containing 5-9% plastic strips performed better than soil samples containing no plastic strips. Therefore, shear strength can assist in resisting deformation under stress caused by the weight of an embankment. Moreover, the friction angle determines the embankment slope stability and the material’s ability to withstand deformation caused by water flow, freeze-thaw cycles, or other environmental factors. On the other hand, the inclusion of the plastic strip enhanced the permeability of black cotton-reinforced soil. This innovative approach may be utilized to successfully address socioeconomic issues, such as recycling waste materials.